A pyrolysis–phosphorization approach to fabricate carbon nanotubes with embedded CoP nanoparticles for ambient electrosynthesis of ammonia. Issue 82 (27th September 2019) - Zhang, Shengbo; Gong, Wanbing; Lv, Yang; Wang, Haojie; Han, Miaomiao; Wang, Guozhong; Shi, Tongfei; Zhang, Haimin
Abstract : The (112) plane dominated CoP nanoparticles in carbon nanotubes (CoP/CNs) fabricated by a pyrolysis-phosphorization approach exhibited superior electrocatalytic NRR activity with a large NH3 yield rate and high faradaic efficiency. Abstract : We report a pyrolysis–phosphorization approach to fabricate carbon nanotubes with embedded CoP nanoparticles (CoP/CNs) using ZIF-67 as a precursor for electrocatalytic nitrogen (N2 ) reduction to ammonia (NH3 ) under ambient conditions. The results demonstrate that the as-synthesized CoP/CNs as electrocatalysts exhibit high electrocatalytic activity toward the N2 reduction reaction (NRR), affording a large NH3 yield rate of 48.9 μg h −1 mgcat. −1 with a faradaic efficiency (FE) of 8.7% at −0.4 V ( vs. RHE) in 0.1 M Na2 SO4 electrolyte. The 15 N isotopic labelling experiments confirm that the NH3 obtained is indeed from the CoP/CN catalyzed NRR process. Our theoretical calculation results reveal that the N2 molecules prefer to be adsorbed on the highly unsaturated three coordinated Co sites of the CoP(112) plane following an associative distal hydrogenation process.